Cleavage and Polyadenylation Specificity Factor 6 Is Required for Efficient HIV-1 Latency Reversal - Yue Zheng (American Society for Microbiology, 2021)
CPSF6 is a cellular factor that regulates cleavage and polyadenylation of mRNAs and participates in HIV-1 infection by facilitating targeting of preintegration complexes to the chromatin. Our observations reveal a second role of CPSF6 in the HIV-1 life cycle that involves regulation of viral transcription through controlling the stability of protein phosphatase 2A, which in turn regulates the phosphorylation/dephosphorylation status of critical residues in CDK9 and Pol II.